PELUANG EFISIENSI PENGGUNAAN DAN BIAYA PUPUK PADA LAHAN SAWAH HASIL ANALISA TANAH (KASUS DI KECAMATAN KESUGIHAN KABUPATEN CILACAP) - D Juanda J.S; Sodiq Jauhari (JURNAL LITBANG PROVINSI JAWA TENGAH, 2005)
Revision of reconunendation on fertilizing technology which always develops is absolutely required, because it is the key in the effortof creating self-supporting of food, especially for rice.One of technologies which can be used as a basic of analysis on recommendationof ricefield fertilizing is through status analysis of the chemical element P and K for ricefield area. So far recommendation on the fertilizing ofricefield P and K still use general recommendation,namely I 00-150 kg SP-36/hectarand 10 kg KCl/hectar, because it has not been based on the status of soil chemical element. The researchstatus of the chemical element P and K, by Puslitbangtanak of Bogor in Central Java Province, at scale I :50.000, has been started in Brebes Regency.Tegal,and then in 200 I it is continued by BPTP of Central Java in Kedung, Tuban Subdistrict, Blom Regency and Masaran Subdistrict and Plupuh ofSragen Regency. Analysis program on the chemical element statusof the ricefield P and Kin 2002 is located i.n KesugihanSubdistrict ofCilacap Regency. The materialsrequired are as follows: Administration Map, scale J :250.000 and I :500.000, Map of Earth I topography scale 1 :250.000, map ofland scale I :250.000 and I :50.000, map ofland usage scale I: 50.000, land drill, surface knife, plastic bucket, plastic cartoon papers, wool string, plastic sack, rafia fibre, permanentmarker and water gerigen, Methodology use comprises: preparation, operation of soil sample taking and analysis ofsoil. In the level of field operational, it comprises consultation withAgriculture Deparunent/BIPP/BPP/KCD. Main Surveyperforms thesarnple talking of'individual soil which is become as sample ofcompbosit sample, l sample of chomposit sample consist of l 0-. 15 sampleof individual soil. The next level is sample of chomposit, which is dried and smoothened and then the contentof potencial P and K is analized by extract ofHCL 25%,the data from the resultofsoil analysis of the contentP and K through 3 status (low criteria,middle and high). Commonly,the result of the status mapping on the riccfield P and K is as follows: there are 168 samples of soil of the chemical element status P; low up to.high of'KesugihanSubdistrict, the low status is 10- 16 mg P :0/100 mg or46J, 156 nectar wide, the middle status is 23 -39 mg P20/100 mgor2079,764 hectars wide; and the high status is 42-86 mg/ JOO g with 1523,017 hectars wide, but the statusoflow chemical elementK is 7 · JO mg K20/ 100 g with 804,926hectarwide the middle status is 11 . i 7 mg/100 g K10 or2228,524 hectars wide and the status of high K is 21-46 mg/100 g K10 with 612,741 hectars wide by doing fertilizing suitable with the result of soil analysis, so the cost can be economized for Rp.523.094.375 per season for the buying of the fertilizerSP-36 and minus Rp. 25.969.230 per planting season for the buying of the fertilizer.KCL, but the using is recoveredof cost over with SP- 36 fertilizer